Strategi Komunikasi Guru dalam Menginternalisasikan Nilai-Nilai Islami Pada Kurikulum SMAIT Buah Hati - Nadiah Fitriana; Ahmad Adnan (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2026)
This study analyzes teachers' communication strategies in internalizing Islamic values within the curriculum at SMAIT Buah Hati and evaluates their effectiveness in shaping students' Islamic character. The research uses a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews with the principal, curriculum vice principal, Islamic education teacher, subject teachers, and students, supported by observation and documentation of school programs. The findings show that the communication strategy is implemented through Islamic value-based lesson planning, integration of Qur'anic verses and hadith in subject materials, persuasive and dialogical interaction, teacher role modeling, and habituation through school culture. Morning dhikr, congregational prayer, Qur'an memorization, mentoring, social service, and written media function as a hidden curriculum that strengthens value internalization. The strategy is effective in improving students' religiosity, discipline, courtesy, responsibility, and social care. Supporting factors include teacher competence, exemplary conduct, integrated curriculum, visionary leadership, parental involvement, and a religious environment, while obstacles include varied teacher competence, limited instructional time, diverse student spiritual backgrounds, and digital media influences.